ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR PERIODE 2017-2020 - Vinna Marcella; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The purpose of this study to determine the effect of capital structure (DER), profitability(ROE), liquidity (CR), firm size (SIZE) and firm growth (GROWTH) on firm value (PBV).This research was conducted in manufacturing companies listed in the Indonesia Stock Exchange during 2017-2020. The sampling technique used purposive sampling method and data processing using Eviews 10 software. In this research, there were 69 companies as samples from 184 companies and were analyzed by multiple linear regression. The results of this study indicate that the effect of capital structure and profitability on firm value is positive and significant. The effect of liquidity on firm value is positive and not significant, and other variables, namely the effect of firm size and firm growth on firm value, are negative and insignificant. The implication of this research is that the firm can be assessed well by the wider community, creditors and investors by increasing the value of the firm.